2020
DOI: 10.1007/s00281-020-00819-8
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of dopaminergic signaling in the cross talk between the renin-angiotensin system and inflammation

Abstract: The renin-angiotensin system (RAS) is a fundamental regulator of blood pressure and has emerged as an important player in the control of inflammatory processes. Accordingly, imbalance on RAS components either systemically or locally might trigger the development of inflammatory disorders by affecting immune cells. At the same time, alterations in the dopaminergic system have been consistently involved in the physiopathology of inflammatory disorders. Accordingly, the interaction between the RAS and the dopamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 145 publications
(192 reference statements)
0
6
0
Order By: Relevance
“…Due to LOS effects on the blood–brain barrier permeability modulation, as [ 34 ] showed in a rat model of angiotensin-II-induced arterial hypertension, LOS could also exhibit modulatory effects on the brain tissues. Thus, we previously showed that RAS modulation using LOS and RAM could improve cognitive performances and socio-affective behavior, while Abiodun and Ola [ 35 ] and Campos and Pacheco [ 36 ] provided an updated perspective of the RAS system in neurodegeneration and inflammation. Moreover, Ahmed et al [ 37 ] and Mirzahosseini et al [ 38 ] even described promising mechanisms in which RAS modulation could prevent progressive cognitive impairments and inflammation following brain-injury-derived neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Due to LOS effects on the blood–brain barrier permeability modulation, as [ 34 ] showed in a rat model of angiotensin-II-induced arterial hypertension, LOS could also exhibit modulatory effects on the brain tissues. Thus, we previously showed that RAS modulation using LOS and RAM could improve cognitive performances and socio-affective behavior, while Abiodun and Ola [ 35 ] and Campos and Pacheco [ 36 ] provided an updated perspective of the RAS system in neurodegeneration and inflammation. Moreover, Ahmed et al [ 37 ] and Mirzahosseini et al [ 38 ] even described promising mechanisms in which RAS modulation could prevent progressive cognitive impairments and inflammation following brain-injury-derived neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The high levels of dopamine, ranging from 1 to 10 μM, in vivo binding to low-affinity dopamine receptors (DRD1 and DRD2) on microglia could exert anti-inflammatory effects by modulating the proinflammatory renin–angiotensin system [ 108 , 109 ], and DRD1 could mediate the autophagic degradation of NLRP3 protein. The low levels of dopamine in the body, ranging from 20 to 500 nM, could selectively stimulate the high-affinity dopamine receptors (DRD3, DRD4, and DRD5), thereby inducing inflammatory responses [ 110 ].…”
Section: Relationship Between Inflammation and Depressionmentioning
confidence: 99%
“…Previous studies from our laboratory and others have involved the brain renin-angiotensin system (RAS) in progression of Parkinson's disease and other neurodegenerative diseases by enhancing neuronal oxidative stress and neuroinflammatory processes (Campos and Pacheco, 2020;Labandeira-Garcia et al, 2013;Labandeira-Garcia et al, 2017;Wright and Harding, 2019). Interestingly (Labandeira-Garcia and Parga, 2022), a recent study has shown that the population of human dopaminergic neurons most vulnerable to degeneration in Parkinson's disease can be identified by their high expression of angiotensin type-1 (AT1) gen (Kamath et al, 2022).…”
Section: Introductionmentioning
confidence: 99%